A Practice-Based Theory of Diversity: Respecifying (In)Equality in Organizations - Janssens, Maddy; Steyaert, Chris (Academy of Management Review, 2019)
In this article we turn to practice theory as a new theoretical lens to better understand the complexity of diversity in organizations. Questioning the field’s ontological dualism between individualism and societism, we engage with practice theory’s relational ontology and its main conceptual and methodological ideas. From this we develop a practice-based theory of diversity, arguing that practices and their connections, not individuals or discourses, are the unit of analysis to best study and understand the social life of a diverse organization. We apply this theoretical lens to (in)equality through two research examples, showing how the practicing of career mentoring is connected to other inequality-(re)producing practices and how the equal social order of a dance organization is accomplished through the situated practice of mixing. In the discussion we highlight the value of a practice theory for diversity. A practice-based theory of diversity renews the research agenda of diversity studies, forwarding postdualistic forms of theorizing, reconceptualizing diversity practices along the theoretical logic of practice, and conceiving of diversity-related phenomena as the net effect of social order–producing practices.